ynthesis and Characterization of 1-Aryl-5-hepta-O-acetyl-β-D-maltosyl-2-S-benzyl-2,4-isodithiobiurets - R. D. Ghuge; S. P. Deshmukh (E-Journal of Chemistry)
The facile synthesis of 1-aryl-5-hepta-o-acetyl-β-D-maltosyl-2-S-benzyl-2,4-isodithiobiurets (IIIa-g) has been achieved by the interaction of 1-hepta-O-acetyl-β–D-maltosyl isothiocyanate (I) with various1-aryl-S-benzyl isothiocarbamides (IIa-g). All the newly synthesized N-maltosylated compounds characterized by elemental analysis, IR, NMR and Mass spectral studies.